Avaliação das alterações sistêmicas e hematológicas em modelo experimental de osteonecrose dos maxilares induzida por ácido zoledrônico - Silva, Paulo Goberlânio de Barros (2013)
Introduction: Several mechanisms have been proposed to explain the induced Osteonecrosis of the Jaw Bisphosphonates (OMB), but there is no consensus about the pathophysiological development of this condition. Objective: To evaluate the effect of systemic and hematologic changes that may interfere with the development of OMB. Methods: After three consecutive weekly venous infusions of zoledronic acid (AZ) (0.04, 0.20, 1,00mg / kg) or saline (control), male Wistar rats (n = 6-7) had their first molars left extracted four weeks after the last administration. A week after extraction extra infusion of AZ or saline (control) was performed, and the animals were sacrificed 28 days after the extraction. The animals were weighed and blood was collected weekly (analysis of variance in body weight and hematologic analysis, respectively) furthermore jaws, liver, spleen, kidney and stomach were removed and examined microscopically. Results: Obervou0se bone necrosis in animals treated with 0.20 and 1.00 mg / kg of AZ under the radiographic and histological aspects (p <0.0001). In both groups there was a significant increase in the number of circulating leukocytes (p <0.0001) compared to the control group and the rates of anemia (p <0.0001) were also higher. There was no liver and kidney toxicity, however the spleen showed increased numbers of hemosiderin pigment deposition in both experimental groups (p = 0.0004), which also showed a significant gastric inflammatory changes (p = 0.0168). Conclusion: The OMB is directly associated with leukocytosis, anemia and probable (hematologic and organ-specific) systemic toxicity.